La vita felice: Arguments For and Against Phenomenological Objectivity and Objectivation in the Reflections of Giovanni Piana and Enzo Paci (Nóema, 2025)
This work focuses on significant reflections by Enzo Paci and Giovanni Piana regarding objectivity and objectification, based on their commentary on selected passages from Edmund Husserl’s phenomenological proposal. In The Crisis, particularly, Husserl underscores the controversy associated with the potential mathematization of essences, which he perceives as influencing modern philosophy and gradually leading to a state of crisis. In this text, Husserl therefore criticises the application of a method deemed illicit according to his proposal for rectifying phenomenology, which could undermine the value of intuition and the historical, progressive acquisition of knowledge. This study highlights the key points of this theoretical review and follows the commentary subsequently provided by Paci and Piana, which uniquely centres on a potential political reading and interpretation of these positions, to which this contribution gives particular attention.
Keywords: Objectivity; Objectivism; Process; Teleology; Intersubjectivity